AZT / ABACAVIR. (2nd April 2021) - Rees, Sharon
Abstract : In this column, Sharon Rees aims to refresh knowledge and interest in some of the commonly used drugs in a series of tweets. This month she is talking about #AZT and the newer NRTI #abacavir